BIOCHEMICAL DETECTION OF APOPTOSIS BY DNA FRAGMENTATION IN THE TISSUES OF THE STOMACH AND KIDNEY UNDER CONDITIONS OF INDUCED STRESS - Komarevtsev, V.M.; Balabanova, K.V.; Kalinin, I.V.; Rudenko, I.V.; Usatov, S.A.; Kazakov, V.Ye.; Komarevtseva, I.O. (World of Medicine and Biology, 2024)
The purpose of the study was to investigate the activity of apoptosis in the gastric mucosa and renal by the level of fragmented DNA under conditions of experimental restraint stress. The restraint stress model was chosen as an experimental model of the pathophysiology of stress-related mucosal disease and acute renal failure in rats. According to the level of fragmented DNA, which indicates the level of apoptosis in the tissues of the gastric mucosa at different times after immobilization stress, the phases of the pathological process can be distinguished. The dynamics of changes in apoptosis activity by the level of fragmented DNA in the tissues of the renal cortex after immobilization stress had a two-phase nature. Experimental immobilization stress has a significant effect on DNA fragmentation levels in the renal medulla. The effects of stress increase during the first two weeks, after which adaptation or recovery processes begin. Even after 21 days, DNA damage levels remain significantly higher than normal, indicating long-term effects of stress on kidney cells.